9514 1404 393
Answer:
3x +y -13 = 0
Explanation:
The perpendicular line will have the variable coefficients swapped and one of them negated. The new constant will be appropriate to the given point.
3(x -4) +1(y -1) = -0
3x +y -13 = 0
_____
Additional comment
The given equation is in "general form", so that is the form of the equation we have given as the answer. This form is convenient in that the general form equation for a line through the origin, ax+by=0, is easily translated to make it pass through a point (h, k): a(x -h) +b(y -k) = 0. Eliminating parentheses puts the equation back into general form.